PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN, TEKANAN KETAATAN, PENGALAMAN AUDITOR SERTA ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK (Studi Empiris pada KAP di Pekanbaru, Batam dan Padang) - Novia Arnia Yanti; Andreas '; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study is to determine Influence of Professionalism, Auditor’s Knowledge for Errors, Obedience Pressure, Experience of Auditor’s and Professional Ethics to Public Accountant’s Judgement of Materiality Levels. Research carried out on Registered Public Accountan’s located in Pekanbaru, Padang and Batam. Purposive sampling method is taken and generates 63 respondents as sample. Statistical analysis which used in this study is multiple regression method by SPSS version 16.00. The result of this study showed that auditor’s knowledge for errors, experience of auditor’s, professional ethics significant influence on public accountant’s judgement of materiality levels. While the professionalism and obedience pressure no effect on public accountant’s judgement of materiality levels. Based on the test result of the coefficient determination, the value of the Adjust R Square is 42.4 % while the remaining 57.6 is influenced by other factors not included in this study.Keywords: Professionalism, Auditor’s Knowledge for Errors, Obedience Pressure, Professional Ethics and Judgement of Materiality Levels.